Enhancing Care of Aged and Dying Prisoners: Is e-Learning a Feasible Approach?. Issue 4 (October 2017) - Loeb, Susan J.; Penrod, Janice; Myers, Valerie H.; Baney, Brenda L.; Strickfaden, Sophia M.; Kitt-Lewis, Erin; Wion, Rachel K.
ABSTRACT: Background: Prisons and jails are facing sharply increased demands in caring for aged and dying inmates. Our Toolkit for Enhancing End-of-life Care in Prisons effectively addressed end-of-life (EOL) care; however, geriatric content was limited, and the product was not formatted for broad dissemination. Prior research adapted best practices in EOL care and aging; but, delivery methods lacked emerging technology-focused learning and interactivity. Purposes: Our purposes were to uncover current training approaches and preferences and to ascertain the technological capacity of correctional settings to deliver computer-based and other e-learning training. Methods: An environmental scan was conducted with 11 participants from U.S. prisons and jails to ensure proper fit, in terms of content and technology capacity, between an envisioned computer-based training product and correctional settings. Results: Environmental scan findings focused on content of training, desirable qualities of training, prominence of "homegrown" products, and feasibility of commercial e-learning. Conclusions/Implications: This study identified qualities of training programs to adopt and pitfalls to avoid and revealed technology-related issues to be mindful of when designing computer-based training for correctional settings, and participants spontaneously expressed an interest in geriatrics and EOL training using this learning modality as long as training allowed for tailoring of materials.